DEVELOPMENT OF DIGITAL ECONOMY IN INDIA AND ITS SOCIO-ECONOMIC IMPACT - Desai, Dr.Savitaben H. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The digital economy in India has developed at a rapid pace in the last two decades. Information technology, mobile internet, digitization, e-commerce, and fintech services have not only changed the ways of production and consumption, but also profoundly influenced the social and economic structure. The purpose of this research is to analyze the development of digital economy, its contribution, and socio-economic impacts. Findings show that while digitalization has increased financial inclusion, employment, punishment, and transparency, on the other hand, challenges of digital divide, cyber security, and inequalities have also emerged.